Economic Exploitation of Children: Returning Child Labor to the World of Education Through Interpersonal Communication Towards Equal Education - Aye Sudarto; Muhamad Bisri Mustofa; Anas Malik (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
Low family incomes force children to support households and become Child Labourers (PA) in the agricultural and household sectors. The agricultural sector is still the main source of income for most Indonesians; at least 70% of the archipelago's population is dependent on the agricultural sector. However, rural poverty remains relatively high. At least 16% of rural areas are poor compared to 9.9% of urban areas. Farm labourers have not been able to benefit significantly from economic growth, as it is undeniable that several problems have caused the agricultural sector to lag behind other sectors. This qualitative study will describe the processes that influence and shift the mindset of children and parents of child laborers to change their mindset and desire to continue their education. Economic exploitation in children is actually carried out by families, for example, by placing, allowing, and telling children to work as a form of economic exploitation. Good economic exploitation will result in good child development, but bad exploitation will have a bad impact on children, including lying, insensitivity, low self-esteem, developmental disorders, oppressing the weak, difficulty forming and interacting with the environment, anxiety, low self-esteem, and personality disorders. Equality education is another way for children to re-enter school. It is necessary to optimise all stakeholders to eliminate child labour and return child labourers to school. It is necessary to strengthen equivalency schools in various places so that they can be reached by children with economic difficulties or difficulties integrating into public schools. Preventive efforts must be made to ensure that children do not drop out of school and are prepared to enter the global workforce, including introducing and raising awareness of the importance of education, as well as providing affordable education to all.